The Regenerative Potential of Therapeutic Ultrasound on Neural Tissue: A Pragmatic Review. Issue 7 (26th May 2020) - Haffey, Paul Ryan; Bansal, Nitin; Kaye, Elena; Ottestad, Einar; Aiyer, Rohit; Noori, Selaiman; Gulati, Amitabh
Abstract: Objectives: Low-intensity ultrasound (LIU)/low-intensity pulsed ultrasound (LIPUS) may influence nerve tissue regeneration and axonal changes in the context of carpal tunnel syndrome (CTS) and in the animal model. The purpose of this pragmatic review is to understand the current knowledge for the effects of low-intensity therapeutic ultrasound in the animal and human model and determine the future directions of this novel field. Design: Pragmatic review. Methods: We performed a literature search of available material using OVID, EmBase, and PubMed for LIU/LIPUS, all of which were preclinical trials, case reports, and case series using animal models. For CTS, a literature search was performed on PubMed (1954 to 2019), CENTRAL (the Cochrane Library, 1970 to 2018), Web of Science (1954 to 2019), and SCOPUS (1954 to 2019) to retrieve randomized controlled trials. Results: Eight articles were discussed showing the potential effects of LIU on nerve regeneration in the animal model. Each of these trials demonstrated evidence of nerve regeneration in the animal model using LIPUS or LIU. Seven randomized controlled trials were reviewed for ultrasound effects for the treatment of carpal tunnel syndrome, each showing clinical efficacy comparable to other treatment modalities. Conclusions: LIU/LIPUS is a promising and noninvasive means of facilitating nerve regeneration in the animal model and in the treatment of carpal tunnel syndrome. Although many of the trials included in this review are preclinical, each demonstrates promising outcomes that could eventually be extrapolated into human studies.